Effect of peer education in school on sexual health knowledge and attitude in girl adolescents - Hatami, Mahnaz (J Educ Health Promot, 2015)
BACKGROUND: Adolescence is associated with so many changes, and to provide sexual health it is necessary for teenagers to learn enough knowledge about the changes and appropriate health behaviors. The attraction of sexual issues in teenagers is associated with more conversations related to sexual matters. Therefore, this study has evaluated the effect of organizing these interactions using peer education in schools on the knowledge and attitude toward sexual health. MATERIALS AND METHODS: This was an interventional study conducted on 282 girl teenagers from high schools of Isfahan that were divided into two groups of intervention and control. Peer education in the intervention group was done through 35 trained teenagers during normal communications in school. Before the training knowledge and attitude of students in both groups were evaluated; then peer education was conducted during 6 weeks through normal communications on the intervention group and then afterward the knowledge and attitude of the students were evaluated again. To analysis of data independent t-test and paired t-test were used. RESULTS: The results showed that the mean score of knowledge and attitudetoward all sexual health dimensions during puberty in the intervention group was significantly higher after the intervention (P < 0.05). In addition, there was a significant difference between the mean score of knowledge and approach toward all the aspects of sexual health of both the studied groups. CONCLUSIONS: The results showed that using peer education in schools informally could enhance the knowledge and approach toward aspects of physical health, sexual behaviors, and social and mental changes among female adolescences and could be applied in schools.